Shapeshifter TDP-43: molecular mechanism of structural polymorphism, aggregation, phase separation and their modulators - Doke, Abhilasha A.; Jha, Santosh Kumar (Biophysical Chemistry, 2023)
TDP-43 is a nucleic acid-binding protein that performs physiologically essential functions and is known to un-dergo phase separation and aggregation during stress. Initial observations have shown that TDP-43 forms het-erogeneous assemblies, including monomer, dimer, oligomers, aggregates, phase-separated assemblies, etc. However, the significance of each assembly of TDP-43 concerning its function, phase separation, and aggregation is poorly known. Furthermore, how different assemblies of TDP-43 are related to each other is unclear. In this review, we focus on the various assemblies of TDP-43 and discuss the plausible origin of the structural het-erogeneity of TDP-43. TDP-43 is involved in multiple physiological processes like phase separation, aggregation, prion-like seeding, and performing physiological functions. However, the molecular mechanism behind the physiological process performed by TDP-43 is not well understood. The current review discusses the plausible molecular mechanism of phase separation, aggregation, and prion-like propagation of TDP-43.
Keywords: Amyloid versus non-amyloid; Coacervation; Environmental conditions; Prion-like seeding; Structural heterogeneity; Thermodynamic and kinetic mechanism

Deciphering the monomeric and dimeric conformational landscapes of the full-length TDP-43 and the impact of the C-terminal domain - Tammara, Vaishnavi; Doke, Abhilasha A.; Jha, Santosh Kumar; Das, Atanu (ACS Chemical Neuroscience, 2024)
The aberrant aggregation of TAR DNA-binding protein 43 kDa (TDP-43) in cells leads to the pathogenesis of multiple fatal neurodegenerative diseases. Decoding the proposed initial transition between its functional dimeric and aggregation-prone monomeric states can potentially design a viable therapeutic strategy, which is presently limited by the lack of structural detail of the full-length TDP-43. To achieve a complete understanding of such a delicate phase space, we employed a multiscale simulation approach that unearths numerous crucial features, broadly summarized in two categories: (1) state-independent features that involve inherent chain collapsibility, rugged polymorphic landscape dictated by the terminal domains, high beta-sheet propensity, structural integrity preserved by backbone-based intrachain hydrogen bonds and electrostatic forces, the prominence of the C-terminal domain in the intrachain cross-domain interfaces, and equal participation of hydrophobic and hydrophilic (charged and polar) residues in cross-domain interfaces; and (2) dimerization-modulated characteristics that encompass slower collapsing dynamics, restricted polymorphic landscape, the dominance of side chains in interchain hydrogen bonds, the appearance of the N-terminal domain in the dimer interface, and the prominence of hydrophilic (specifically polar) residues in interchain homo- and cross-domain interfaces. In our work, the ill-known C-terminal domain appears as the most crucial structure-dictating domain, which preferably populates a compact conformation with a high beta-sheet propensity in its isolated state stabilized by intrabackbone hydrogen bonds, and these signatures are comparatively faded in its integrated form. Validation of our simulated observables by a complementary spectroscopic approach on multiple counts ensures the robustness of the computationally predicted features of the TDP-43 aggregation landscape.
Keywords: chain collapsibility; domain-wisefluctuation; electrostatic dominance; hydrogen bond switchability; long-range crosstalk; persistent beta-character; protagonistic C-terminal domain; rugged phase space

Electrostatics choreographs the aggregation dynamics of full-length TDP-43 via a monomeric amyloid precursor - Doke, Abhilasha A.; Jha, Santosh Kumar (Biochemistry, 2024)
TDP-43 is a ubiquitously expressed, multidomain functional protein that is distinctively known to form aggregates in many fatal neurodegenerative disorders. However, the information for arresting TDP-43 aggregation is missing due to a lack of understanding of the molecular mechanism of the aggregation and structural properties of TDP-43. TDP-43 is inherently prone to aggregation and has minimal protein solubility. Multiple studies have been performed on the smaller parts of TDP-43 or the full-length protein attached to a large solubilization tag. However, the presence of co-solutes or solubilization tags is observed to interfere with the molecular properties and aggregation mechanism of full-length TDP-43. Notably, this study populated and characterized the native, dimeric state of TDP-43 without the interference of co-solutes or protein modifications. We observed that the electrostatics of the local environment is capable of the partial unfolding and monomerization of the native dimeric state of TDP-43 into an amyloidogenic molten globule. By employing the tools of thermodynamics and kinetics, we reveal the structural characteristics and temporal order of the early intermediates and transition states during the transition of the molten globule to beta-rich, amyloid-like aggregates of TDP-43, which is governed by the electrostatics of the environment. The current advanced understanding of the nature of native and early aggregation-prone intermediates, early steps, and the influence of electrostatics in TDP-43 aggregation is essential for drug design.

Identification of a hidden, highly aggregation-prone intermediate of full-length TDP-43 that triggers its misfolding and amyloid aggregation - Doke, Abhilasha A.; Jha, Santosh Kumar (Biochemistry, 2024)
In cells, TDP-43 is a crucial protein that can form harmful amyloid aggregates linked to fatal and incurable human neurodegenerative disorders. Normally, TDP-43 exists in a smaller soluble native state that prevents aggregation. However, aging and stress can destabilize this native state, leading to the formation of disease-causing amyloid aggregates via the formation of partially unfolded, high-energy intermediates with a greater tendency to aggregate. These intermediates are crucial in the early stages of amyloid formation and are challenging to study due to their low stability. Understanding the structure of these early aggregation-prone states of TDP-43 is essential for designing effective treatments for TDP-43 proteinopathies. Targeting these initial intermediates could be more effective than focusing on fully formed amyloid aggregates. By disrupting the aggregation process at this early stage, we may be able to prevent the progression of diseases related to TDP-43 aggregation. Hence, we decided to uncover the hidden, high-energy intermediates in equilibrium with the native states of TDP-43 by modulating the thermodynamic stability of the soluble native dimer (N form) and monomeric molten globular state (MG form) of full-length TDP-43. The thermodynamic modulation performed in the current study successfully revealed the highly aggregation-prone intermediate of full-length TDP-43, i.e., PUF. Moreover, we observed that along with high aggregation propensity, the aggregation kinetics and mechanisms of PUF differ from previously identified intermediates of full-length TDP-43 (the MG and I forms). The information regarding the initial aggregation-prone state of full-length TDP-43 could lead to therapies for amyloid diseases by halting early protein aggregation.

Structural and mechanistic heterogeneity of the phase separation and aggregation of full-length TDP-43 is governed by environmental conditions - Doke, Abhilasha A.; Kirmire, Mona S.; Jha, Anjali; Jha, Santosh Kumar (ACS Chemical Neuroscience, 2026)
TAR DNA-binding protein 43 (TDP-43) is an essential physiological protein implicated in several fatal neurodegenerative disorders. Interestingly, the nature of TDP-43 aggregates varies across patients and disease conditions, suggesting an underlying heterogeneity in its self-assembly behavior. In this study, we investigated two native-like states of full-length TDP-43: the native dimer (N form) and the native-like oligomer (O form). These are compact, folded states with similar secondary structures but differ in size. We found that the N and O forms respond differently to external perturbations and form distinct self-assemblies under stress conditions. Under electrostatic stress, both N and O forms undergo phase separation but produce condensates with markedly different morphologies and dynamics. The underlying mechanisms driving their phase separation are different. Under thermal stress, both forms convert into amyloid aggregates, but again with clearly different morphologies, biochemical properties, and aggregation pathways. These results demonstrate that multiple conformations of TDP-43 respond to distinct perturbations by assembling into structurally and mechanistically different higher-order assemblies. Our findings highlight how the interplay among the structural state, solvation environment, and self-assembly mechanism governs the heterogeneity of TDP-43 assemblies, offering new insights into their physiological roles and pathological relevance. This study suggests that the heterogeneity observed in patients associated with TDP-43 aggregation may arise from differences in the cellular stresses experienced by the protein and the corresponding assembly mechanisms engaged.
Keywords: Amyloid-like aggregation; molecular mechanism of phase separation; native-like phase separation; Self-assembly